Pharmacological treatment of inhalation injury after nuclear or radiological incidents: The Chinese and German approach - Tian-Tian Yan; Guo-An Lin; Min-Jie Wang; Andreas Lamkowski; Matthias Port; Alexis Rump (Military Medical Research, 2019)
Abstract Inhalation injury is often associated with burns and significantly increases morbidity and mortality. The main toxic components of fire smoke are carbon monoxide, hydrogen cyanide, and irritants. In the case of an incident at a nuclear power plant or recycling facility associated with fire, smoke may also contain radioactive material. Medical treatments may vary in different countries, and in this paper, we discuss the similarities and differences in the treatments between China and Germany. Carbon monoxide poisoning is treated by 100% oxygen administration and, if available, hyperbaric oxygenation in China as well as in Germany. In addition, antidotes binding the cyanide ions and relieving the respiratory chain are important. Methemoglobin-forming agents (e.g., nitrites, dimethylaminophenol) or hydroxocobalamin (Vitamin B12) are options. The metabolic elimination of cyanide may be enhanced by sodium thiosulfate. In China, sodium nitrite with sodium thiosulfate is the most common combination. The use of dimethylaminophenol instead of sodium nitrite is typical for Germany, and hydroxocobalamin is considered the antidote of choice if available in cases of cyanide intoxications by fire smoke inhalation as it does not further reduce oxygen transport capacity. Systematic prophylactic use of corticosteroids to prevent toxic pulmonary edema is not recommended in China or Germany. Stable iodine is indicated in the case of radioiodine exposure and must be administered within several hours to be effective. The decorporation of metal radionuclides is possible with Ca (DTPA) or Prussian blue that should be given as soon as possible. These medications are used in both countries, but it seems that Ca (DTPA) is administered at lower dosages in China. Although the details of the treatment of inhalation injury and radionuclide(s) decorporation may vary, the general therapeutic strategy is very similar in China and Germany.